Aggression Dimensions in Students with Autism - Elsayed S. Elkhamisi; Maryam Almutery (European Scientific Journal, ESJ, 2018)
The current study is intended to explore the prevalence of aggression level of students with autism based on gender, age, and intellectual state. The study sample is composed of parents for (108) of children with autism. These students are aged 5-16 years old who have been attending the autism centers in the State of Kuwait. The current study has utilized a three-dimensional aggression scale, which includes aggression toward others, aggression toward self, and aggression toward things. The result of the study reveals that among the participant's aggression toward others has been ranked the highest on subscale, followed by aggression toward self, and lastly aggression toward things. The study further exposed that the most significant aspects of aggression were explicit obstinacy and refusal when asking the participant to perform an action, the act of pinching others in a state of anger, kicking others without any legit or obvious reason, throwing himself on the floor, and hitting himself with his hand or any other part of his body. In addition, the results of the study suggests that there are a statistically significant differences based on gender in aggression toward things, which is in favour of female. No statistically significant difference has been observed based on gender on aggression toward others. As per the total score of aggression scale, there is no statistically significant difference found based on age or intellectual state of all aggression subscales.